A Novel Mutation of Transferrin Receptor 2 in a Chinese Pedigree With Type 3 Hemochromatosis: A Case Report - Tang, Shan; Bai, Li; Gao, Yuan; Hou, Wei; Song, Wenyan; Liu, Hui; Hu, Zhongjie; Duan, Zhongping; Zhang, Liaoyun; Zheng, Sujun (Frontiers in Genetics, 2022)
Type 3 hereditary hemochromatosis (HH) is a rare form of HH characterized by genetic mutation in the TFR2 gene. Clinical features reported in patients with type 3 HH include abnormal liver function, liver fibrosis, cirrhosis, diabetes, hypogonadism, cardiomyopathy, and skin pigmentation. Since its original description in 2000, 33 pathogenic TFR2 mutations associated with HH have been described until now. Here, we first reported a Chinese pedigree of TFR2-related hemochromatosis with a novel compound heterozygous mutation c.1288G>A(p.G430R)/c.960T>A(p.Y320X). Interestingly, different phenotypes were reported although the proband and his sister share the same gene mutation. This inconsistency between genotypes and phenotypes indicates multifactorial etiology contributes to the development of HH. Our report broadens the mutation spectrum of the TFR2 gene associated with HH.